Geographic Distribution of HCV Genotypes and Efficacy of Direct-Acting Antivirals in Chronic HCV-Infected Patients in North and Northeast China: A Real-World Multicenter Study. (29th April 2022) - Li, Wencong; Liang, Jing; An, Jihong; Liu, Lingdi; Hou, Yihui; Li, Lu; Zhao, Wen; Cui, Luyao; Xue, Ningning; Al-Dhamin, Zaid; Han, Tao; Nan, Yuemin; et al.
Abstract : Objective . To assess the geographic distribution of HCV genotypes, effectiveness, and safety of DAA treatment for HCV-infected patients in North and Northeast China. Methods . The geographic distribution of HCV genotypes was analyzed in 2162 patients recruited from April 2018 to February 2021. Sustained virologic response rates at 12 (SVR12) or 24 (SVR24) weeks posttreatment and safety were analyzed in 405 patients who completed DAA treatment according to patient baseline characteristics and treatment. Results . Four genotypes and six subtypes were identified as follows: 1b (1187, 54.90%), 2a (790, 36.54%), 3a/b (134, 6.20%), 6a/n (44, 2.04%), mixed genotypes (2a-6a or 2a-3a) (7, 0.32%). Overall, 99.01% patients achieved SVR12, while 98.43% achieved SVR24. All patients treated with elbasvir/grazoprevir (EBR/GZR), sofosbuvir/velpatasvir ± ribavirin (SOF/VEL ± RBV), and SOF/ledipasvir (LDV) achieved SVR12 or SVR24; 92.86% SVR12 and 95.83% SVR24 were observed in patients using SOF + RBV. SVR12 was higher in noncirrhosis versus compensated cirrhosis patients (100% vs. 97.09%, p = 0.022 ). No severe drug-related adverse event was observed. Conclusions . Genotypes 1b and 2a were dominant subtypes in North and Northeast China. The approved drug regimens EBR/GZR and SOF/LDV for subtype 1b and SOF/VEL for nongenotype 1b are the optimal effective and safety profile.